(untitled) (Dermatology Reports, 2025)
Ceftriaxone is a widely used third-generation cephalosporin antibiotic known for its efficacy and safety. However, hypersensitivity reactions, including rare cases of generalized bullous fixed drug eruption (GBFDE), have been reported. We present the case of a 68-year-old female with a history of multiple comorbidities who developed a generalized bullous drug eruption two days after initiating intravenous ceftriaxone for a suspected respiratory infection. Clinical evaluation revealed extensive bullae and erythematous patches sparing mucous membranes, with histopathology confirming drug-induced epidermal changes. Direct immunofluorescence ruled out autoimmune bullous disorders. Prompt discontinuation of ceftriaxone, systemic corticosteroids, and supportive topical treatments led to marked clinical improvement. This case underscores the importance of recognizing rare but severe cutaneous reactions to ceftriaxone. Early diagnosis and intervention are crucial to minimizing complications and ensuring favorable outcomes.